New entoproct-polychaete association recorded in the Bay of Bengal, southeastern coast of India - Bharathidasan, Veeraiyan; Borisanova, Anastasia O.; Sarathy, Palanivel Partha; Murugesan, Perumal (Zootaxa, 2022)
The solitary entoproct species, Loxosomella diopatricola is recorded from the Bay of Bengal, southeastern coast of India. The species was found on the eunicid polychaete Diopatra sp. collected from depth of 15 m. Loxosomella diopatricola is a medium-sized species with average body length up to 396 µm, eight tentacles and oval in calyx shape. The Loxosomella diopatricola was first time recorded in India. A list of all Loxosomella species associated with polychaetes is given.
World Polychaeta Database (WPolyD).